THE USE OF IRONY AS A FACE-SAVING STRATEGY IN THE MEMOIR "I’M GLAD MY MOM DIED" BY JENNETTE MCCURDY - de Assis Torres, Déborah (Inventário, 2024)
This article seeks to examine how irony functions as a politeness strategy to preserve the protagonist’s face in the best-seller memoir I’m Glad My Mom Died (2022) by Jennette McCurdy. To accomplish this, two excerpts are analyzed in light of the concept of irony stated by Hutcheon (1992, 1994), Spencer-Oatey’s (2005) rapport management framework, and the types of faces discussed by Culpeper (2011). The samples illustrate the use of the aforementioned figured speech as a way of maintaining the face of the main character’s face by preventing her from creating an inharmonious relationship with her mother. Therefore, irony is used as a tool to enhance the general storytelling experience by enabling the development of more complex characters and relationships between them. Finally, the research also indicates the value of utilizing literature as pragmatic data, as it allows a comprehensive analysis of linguistic concepts found that are seen in real-world situations as well.